2021
DOI: 10.1101/2021.07.27.453956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A SUMO-dependent regulatory switch connects the piRNA pathway to the heterochromatin machinery in Drosophila

Abstract: Nuclear Argonaute proteins, guided by small RNAs, mediate sequence-specific heterochromatin formation. The molecular principles that link Argonaute-small RNA complexes to cellular heterochromatin effectors upon binding to nascent target RNAs are poorly understood. Here, we elucidate the mechanism by which the PIWI interacting RNA (piRNA) pathway connects to the heterochromatin machinery in Drosophila. Piwi-mediated stabilization of the corepressor complex SFiNX on chromatin leads to SUMOylation of its subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…PIWI interacting RNAs (piRNAs) and long non-coding RNAs (lncRNAs) are also influenced by SUMOylation. Several studies in Drosophila have demonstrated the role of SUMOylation in primary piRNA biogenesis (Muerdter et al, 2013) and piRNA-guided transcriptional silencing and heterochromatin formation (Mugat et al, 2020;Ninova et al, 2020;Andreev et al, 2022;ElMaghraby et al, 2022). Moreover in C. elegans, PIE-1 is itself modified by SUMO and acts as a SUMO E3 together with the conserved SUMO-E3 GEI-17/PAIS1 to promote piRNA-dependent silencing.…”
Section: Non-coding Rna Metabolismmentioning
confidence: 99%
“…PIWI interacting RNAs (piRNAs) and long non-coding RNAs (lncRNAs) are also influenced by SUMOylation. Several studies in Drosophila have demonstrated the role of SUMOylation in primary piRNA biogenesis (Muerdter et al, 2013) and piRNA-guided transcriptional silencing and heterochromatin formation (Mugat et al, 2020;Ninova et al, 2020;Andreev et al, 2022;ElMaghraby et al, 2022). Moreover in C. elegans, PIE-1 is itself modified by SUMO and acts as a SUMO E3 together with the conserved SUMO-E3 GEI-17/PAIS1 to promote piRNA-dependent silencing.…”
Section: Non-coding Rna Metabolismmentioning
confidence: 99%